2009
DOI: 10.1002/ptr.2520
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of enteropathogenic Escherichia coli adhesion on host epithelial cells by Holarrhena antidysenterica (L.) WALL.

Abstract: Bacterial adhesion is the first step in the sequence of events leading to infection. Previous data are available on the effect of Holarrhena antidysenterica on antidiarrhoeal and antibacterial action, but there is little information on the mechanism of action of the various aspects of EPEC-induced diarrhoea, namely adherence and translocation of the effector molecule to intestinal epithelial cells. The aim of the present study was to investigate the effects of alkaloids of Holarrhena antidysenterica (AHA) on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Holarrhena antidysenterica is of interest since the extract at 7.8 to 62.5 μg/ml possessed no intrinsic antibacterial activity, but in combination with sub-MIC of novobiocin led to a marked decrease in the bacterial growth. Alkaloids were proposed as active principles of the plant that possessed antibacterial activity on S. aureus S. epidermidis Streptococcus faecalis B. subtilis Escherichia coli , and Pseudomonas aeruginosa [27-29]. Some of the alkaloids such as pubadysone, pubescine, norholadiene, pubescimine, puboestrene, pubamide, and naringenin was isolated form bark, seeds, and leaves of this plant [30-32].…”
Section: Resultsmentioning
confidence: 99%
“…Holarrhena antidysenterica is of interest since the extract at 7.8 to 62.5 μg/ml possessed no intrinsic antibacterial activity, but in combination with sub-MIC of novobiocin led to a marked decrease in the bacterial growth. Alkaloids were proposed as active principles of the plant that possessed antibacterial activity on S. aureus S. epidermidis Streptococcus faecalis B. subtilis Escherichia coli , and Pseudomonas aeruginosa [27-29]. Some of the alkaloids such as pubadysone, pubescine, norholadiene, pubescimine, puboestrene, pubamide, and naringenin was isolated form bark, seeds, and leaves of this plant [30-32].…”
Section: Resultsmentioning
confidence: 99%
“…Paste Oral Stomach upset (Biswas et al, 2010) No citation found Desmodium triflorum Paste Oral Stomach ache (Tirkey, 2006); piles (Rajith and Ramachandran, 2010) Anthelmintic (Raj, 1975) (Sen et al, 2011) Gut motility disorders ; antienteric bacterial (Ballal et al, 2001;Kavitha and Niranjali, 2009) Hygrophila auriculata…”
Section: Desmodium Pulchellummentioning
confidence: 97%
“…Pharmacological evaluation has indicated activation of histamine receptors and Ca (þþ) channel blockade are responsible for the anti-GD activity of Holarrhena antidysenterica . Adhesion of the enteric bacteria Escherichia coli on host epithelial cells was found to be inhibited by the same plant (Kavitha and Niranjali, 2009). Aegle marmelos roots extracted in chloroform has shown efficacy as an antidiarrheal agent assessed by in vitro and in vivo studies (Mazumder et al, 2006).…”
Section: Pharmacological Relevancementioning
confidence: 98%
“…Bark of H. antidysenterica is in use for treating diarrhea in traditional/ alternative medicine practices either in India or elsewhere in the world (Kavitha et al, 2009). The MIC and MBC values were found to be 2 and 3 mg/ml respectively.…”
Section: Results and Discussion:-mentioning
confidence: 99%